2005
DOI: 10.1080/17453670510041529
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic compression plates for Vancouver type B periprosthetic femoral fractures

Abstract: Background There is no consensus on the best surgical treatment of periprosthetic femoral fractures. We report our experience with a dynamic compression plate.Patients and methods We reviewed the results of 18 periprosthetic femoral fractures treated with open reduction and internal fixation using the dynamic compression plate (DCP). There were 7 Vancouver type B1, 2 type B2 and 9 type B3 fractures. 16 cases had previously undergone at least one revision procedure. In addition to a DCP plate, all B2 and B3 fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The inherently unstable Vancouver type-B1 periprosthetic fracture is especially challenging in hip arthroplasty performed with cement, which was the type of femoral stem fixation used in all fourteen of these patients. Several authors have reported a union rate ranging from 33% to 100% with different surgical approaches 6,8,9,[14][15][16][17][18] . The loss of endosteal healing potential and the soft-tissue stripping required for the placement of struts, wires, and plates could have played an important role in the failures in this series.…”
Section: Discussionmentioning
confidence: 99%
“…The inherently unstable Vancouver type-B1 periprosthetic fracture is especially challenging in hip arthroplasty performed with cement, which was the type of femoral stem fixation used in all fourteen of these patients. Several authors have reported a union rate ranging from 33% to 100% with different surgical approaches 6,8,9,[14][15][16][17][18] . The loss of endosteal healing potential and the soft-tissue stripping required for the placement of struts, wires, and plates could have played an important role in the failures in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Despite different classification systems and treatment methods, the ideal solution for this entity has always been a dilemma [7]. In recent years great advances in prosthetic designs such as distal locking modular revision prosthesis, fixed angle locking plates, and usage of cortical onlay grafts have improved the outcomes of these fractures [6,11,18,19]. Our study examined the demography, patterns of fracture, treatment modalities and rate of failure in patients having operative treatment for postoperative periprosthetic fracture of femur.…”
Section: Discussionmentioning
confidence: 99%
“…2 These authors and others have suggested that plates may be used, but only in addition to allograft strut fixation. 2,4,[13][14][15][16] We have demonstrated that when bone stock is sufficient, as generally occurs in Vancouver type-B1 fractures, broad metal plate fixation without bone graft is as good as allograft strut fixation and may be preferable. Accurate reduction and stable fixation, with preservation of the blood supply and timely functional rehabilitation, lead to a high rate of early union.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have pointed out several theoretical concerns about plating alone for fixation of peri-prosthetic fractures. 2,4,[13][14][15][16] There may be limited space for screws around the implant proximally, and this may be worse with large canal-filling, uncemented femoral components. 1,9 It has been postulated that screw fixation may damage the cement mantle around a cemented femoral component, produce adverse stress risers around the screws and cause stress shielding under the plate and damage to the stem.…”
Section: Discussionmentioning
confidence: 99%